A study of the effect of pre-radiation on healing of surgical wounds in the treatment of cancers of the head and neck - Dasgupta, Sayandev; Dasgupta, Arup; Sen, Supratik; Sen, Sukanta; Dutta, P. K.; Sen, Samir Kr (International Journal of Research in Medical Sciences, 2016)
Background: Radiation therapy is an established modality in the treatment of head and neck cancer patients. It is used alone or in combination with surgery and chemotherapy. Although radiotherapy is useful to affect tumour death, it also exerts a deleterious effect on surrounding normal tissues. These effects are either acute or can manifest months or years after the treatment. The chronic wounds are a result of impaired wound healing. Compromised wound healing in irradiated tissues is a common and challenging clinical problem. Methods: A prospective observational study was done in a tertiary care teaching institute, Kolkata. The effect of radiation on surgery of cancers of head and neck was studied in 50 patients. The patients were divided into 2 groups of 25 each. The cases in the first group were irradiated prior to surgery and those on the second group were operated upon without any pre-radiation. Results: The highest incidence of wound complications in those patients who were operated upon within 2 weeks to 6 months of completion of RT (83.33%). Patients who had their blood Hb level at or above 11 gm% developed less number of wound complications (34.78%) as compared to those who had their blood Hb level between 8-11 gm% where complication rate was 48.15%. Those patients who had their oral cavity or pharynx opened during surgery had a much higher incidence of wound complications (54.54%) than whose oral cavity or pharynx were not interfered with (17.64%). Wound infection was 36% in the irradiated group and 12% in the non-irradiated group. Separation of wound edges or skin necrosis followed in 28% cases in the pre-radiated group and in 8% cases in the non-pre-radiated group. Conclusions: Radiotherapy is an integral modality of head and neck cancer therapy. Compromised wound healing is an important side effect of radiation therapy. All sorts of local complications as wound infection and necrosis, or ocutaneous fistulae, carotid artery perforation etc. are more pronounced in patients, who received prior radiotherapy. The complication of surgery after radiotherapy was found to be more pronounced between 2 weeks to 6 months in this series.